Admission Grades as Predictors of Medical Students’ Academic Performance: A Cross-Sectional Study from Saudi Arabia - Ali Hendi; Mohammed S. Mahfouz; Ahmad Y. Alqassim; Anwar Makeen; Mohammed Somaili; Mohammed O. Shami; Abdellh A. Names; Alaa Darraj; Areej Kariri; Asma Ashiri; Abdulaziz H. Alhazmi (European Journal of Investigation in Health, Psychology and Education, 2022)
Background: Admission to medical school is competitive, and different countries use various tests in addition to high school grades to minimize selection bias. A few studies have been conducted to evaluate the usefulness of these tests as predictors for students’ academic performance. In this article, we aimed to assess factors that influenced students’ grades in medical school. Methods: A cross-sectional study included all students who graduated from the Faculty of Medicine at Jazan University between 2018 and 2020. Scores of the included participants were extracted from the registry of Jazan University, and additional questions about study habits were completed by the included students. Descriptive, univariate, and multivariate analyses were performed for the factors that impacted academic performance. Results: There were 331 included candidates, and the majority of them were female (53%). About 60% of the participants were medical residents at the time of the study, and 40% were interns. Univariate and multivariate analyses indicated that grades in high school and the pre-requisite tests were positively associated with students’ academic performance. Further, studying more than two hours per day was positively correlated with better grades in medical school. Conclusion: Scores of the admission tests can serve as predictors for student performance in medical school. National studies are deemed essential to evaluate additional admission tests for medical school, an action that would minimize selection bias.